CRIMALDDI: a co-ordinated, rational, and integrated effort to set logical priorities in anti-malarial drug discovery initiatives - Boulton, Ian C.; Nwaka, Solomon; Bathurst, Ian; Lanzer, Michael; Taramelli, Donatella; Vial, Henri; Doerig, Christian; Chibale, Kelly; Ward, Steve A. (Malaria journal, 2010)
Despite increasing efforts and support for anti-malarial drug R&D, globally anti-malarial drug discovery and development remains largely uncoordinated and fragmented. The current window of opportunity for large scale funding of R&D into malaria is likely to narrow in the coming decade due to a contraction in available resources caused by the current economic difficulties and new priorities (e.g. climate change). It is, therefore, essential that stakeholders are given well-articulated action plans and priorities to guide judgments on where resources can be best targeted.
Gesehen am 15.02.2023